Efficacy and safety of first-line PD-1/PD-L1 inhibitor in combination with CTLA-4 inhibitor in the treatment of patients with advanced non-small cell lung cancer: a systemic review and meta-analysis - Zhao, Huimin; Huang, Shanshan; Wu, Jianyu; Lu, Yanlan; Zou, Yue; Zeng, Haijian; Li, Chunlan; Wang, Jin; Zhang, Xiaochen; Duan, Siliang; Liang, Weiming (Frontiers in Immunology, 2025)
IntroductionThe combination of PD-1/PD-L1 inhibitor with CTLA-4 inhibitor for advanced non-small cell lung cancer(NSCLC) is presently a significant area of research, however its clinical application remains contentious. This meta-analysis aimed to assess the efficacy and safety of first-line PD-1/PD-L1 inhibitor in combination with CTLA-4 inhibitor (CP) in the treatment of patients with advanced NSCLC.MethodsA systemic search was conducted in four databases (PubMed, Cochrane library, Embase, and Web of Science) from their establishment until January 17, 2024, for randomized controlled trials that investigated the use of the first-line PD-1/PD-L1 inhibitor plus CTLA-4 inhibitor in patients with advanced NSCLC. Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs) were subjected to meta-analyses.ResultsTotally 7 eligible randomized controlled trials including 4682 people were included. Two comparative analyses were performed: CP versus chemotherapy, CP versus PD-1/PD-L1 inhibitor (P). Compared with the chemotherapy group, CP improved OS (HR: 0.84, 95% CI: 0.75-0.94, p<0.05) but not PFS (HR: 0.94, 95%CI: 0.73-1.20, p = 0.63) or ORR (OR: 1.16, 95% CI: 0.79-1.71, p = 0.45). In terms of toxicity, CP had slightly fewer any AEs compared to chemotherapy (RR: 0.94, 95% CI: 0.91-0.97; p<0.05). Compared to the P group, there was no significant difference in OS (MD: -0,25, 95% CI: -2.47-1.98, p = 0.83), PFS (MD: -0.91, 95% CI: -3.19-1.36, p = 0.43), and ORR (OR:1.05, 95% CI. 0.80-1.36, p = 0.73). Subgroup analysis revealed that CP provided superior OS compared with P in patients with PD-L1 expression < 1%.ConclusionCP was a feasible and safe first-line therapy for patients with advanced NSCLC. Specifically, CP may function as a therapeutic alternative for individuals with low or negative PD-L1 expression, resulting in enhanced long-term outcomes compared to chemotherapy or P. Further randomized controlled trials with prolonged follow-up periods are necessary to validate these results, particularly focusing on efficacy in patients with differing PD-L1 expression levels, to improve the stratified implementation of immunotherapy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024621116, identifier CRD42024621116.